Treatment of Nail Psoriasis with Intralesional Triamcinolone Acetonide Using a Needle-Free Jet Injector: A Prospective Trial. Issue 1 (January 2014) - Nantel-Battista, Melissa; Richer, Vincent; Marcil, Isabelle; Benohanian, Antranik
Background: Treating nail psoriasis is challenging. Corticosteroid matrix injection with needle is a conventional treatment but pain is often a limitation. Objective: Evaluate efficacy and safety of triamcinolone acetonide needle-free injection with the Med-Jet MBX in psoriatic fingernail. Methods: Seventeen patients were enrolled between January 2012 and January 2013. Four treatments sessions were scheduled every 4 ± 1 weeks. Clinical efficacy was evaluated according to Nail Psoriasis Severity Index (NAPSI) score of target nail differences before and after the treatment. Results: Mean baseline NAPSI score was 6.5 on an 8-point scale (95% confidence interval [CI] 5.652–7.348) and mean final NAPSI score was 2.8 on an 8-point scale (95% CI 1.859–3.741), demonstrating statistically significant treatment efficacy ( p =.0007). NAPSI score for target nail from baseline to end of treatment was decreased by 46.25%. Conclusion: Treatment with triamcinolone acetonide delivered by Med-Jet MBX is a safe, minimally painful and effective treatment for nail psoriasis.